Studies of the features of the sorption of an europium by natural and synthetic zeolites for using it in the nuclear energy - Levenets, V.V.; Lonin, A.Yu.; Omelnik, O.P.; Shchur, A.O. (Вопросы атомной науки и техники, 2020)
A technique of quantitative determination of europium by proton-induced X–ray emission (PIXE) using of 1.6 MeV energy and measurement of the characteristic europium Lα–shell X–rays is developed. The possibility of using carbon substrates for the preparation of europium targets to be subjected to 1.6 MeV proton irradiat ion was studied. A linear dependence of the quantitative content and the emission intensity of the Lα–shell of europium is obtained. The use of europium as a natural analogue was applied to the study of the americium sorption from aqueous solutions by natural and synthetic zeolites under static conditions. It has been established that the europium sorption coefficient (Ks) for clinoptilolite is 72.7% that is twice as high the Ks for synthetic zeolites NaA Ks– 36.8%) and NaX (Ks – 25.2%). The effect of competing sodium ions on europium sorption by zeolites has been studied. Розроблено методику кількісного визначення європію за допомогою протон–індукованого рентгенівського випромінювання (ХРВ) з використанням енергії 1,6 МеВ і реєстрацією характеристичного рентгенівського випромінювання Lα–оболонки європію. Вивчено можливість використання вуглецевих підкладок для приготування мішеней, що містять європій для опромінення протонами з енергією 1,6 МеВ. Отримана лінійна залежність кількісного вмісту та інтенсивності випромінювання Lα–оболонки європію. Досліджена сорбція європію як імітатора америцію з водних розчинів природним і синтетичними цеолітами в статичних умовах. Встановлено, що коефіцієнт сорбції європію (Ks) для кліноптилоліту становить 72,7%, що в два рази вище Ks для синтетичних цеолітів NaA (Ks – 36,8%) і NaX (Ks – 25,2%). Вивчено вплив конкуруючих іонів натрію на сорбцію європія цеолітами. Разработана методика количественного определения европия с помощью протон–индуцированного рентгеновского излучения (ХРИ) с использованием энергии 1,6 МэВ и регистрацией характеристического рентгеновского излучения Lα–оболочки европия. Изучена возможность использования углеродных подложек для приготовления мишеней, содержащих европий, для облучения протонами с энергией 1,6 МэВ. Получена линейная зависимость количественного содержания и интенсивности излучения Lα–оболочки европия. Исследована сорбция европия как имитатора америция из водных растворов природным и синтетическими цеолитами в статических условиях. Установлено, что коэффициент сорбции европия (Ks) для клиноптилолита составляет 72,7%, что в два раза выше Ks для синтетических цеолитов NaA (Ks – 36,8%) и NaX (Ks – 25,2%). Изучено влияние конкурирующих ионов натрия на сорбцию европия цеолитами